Porcine Epidemic Diarrhea Virus Surface Decontamination Strategies Using Chemical Sanitizing to Reduce the Quantity of PEDV RNA on Feed Manufacturing Surfaces with Environmental Swabbing - M. Muckey; S. S. Dritz; J. C. Woodworth; C. R. Stark; J. Bai; Jianqiang Zhang; Phillip Charles Gauger; Rodger G. Main; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2016)
Porcine Epidemic Diarrhea virus (PEDV) is a possible hazard in feed mills that could impact pig health. If the virus enters a feed mill, it quickly becomes widely distributed and is difficult to decontaminate from surfaces.6,7 The objective of this study was to evaluate a variety of liquid and dry chemical treatments that could be used as sanitizers to reduce the amount of PEDV found on feed manufacturing surfaces in mills. This experiment was replicated 3 times and was designed in a 5 × 10 factorial with main effects of 5 different feed manufacturing surfaces and 10 sanitizing treatments. Surfaces included stainless steel, plastic, rubber, woven polypropylene tote bag, and sealed concrete coupons (4 × 4 in). One mL (1×105 TCID50/mL) of stock PEDV was applied to each surface and allowed to dry completely for 60 min. Next, a mitigation treatment was applied for 15 min: 1) no sanitation treatment (control); 2) untreated rice hulls; 3) rice hulls treated with formaldehyde-based commercial product (Sal CURB; Kemin Inc., Des Moines, IA); 4) liquid formaldehyde-based commercial product (Sal CURB; Kemin Inc., Des Moines, IA); 5) dry commercial benzoic acid and probiotic blend (VevoVitall and CRINA; DSM Nutritional Products Inc., Parsippany, NJ); 6) liquid ammonium chloride, isopropanol, and hydrogen peroxide-based commercial food-grade sanitizer (DrySan Duo; Ecolab, St. Paul, MN); 7) liquid hydrogen peroxide commercial product (INTERvention; Virox Technologies Inc. Ontario, Canada); 8) liquid quaternary ammonium glutaraldehyde commercial product (Synergize; Preserve International, Reno NV); 9) liquid sodium hypochlorite commercial sanitizer (Bleach; Clorox, Oakland, CA); and 10) liquid medium chain fatty acid blend of caprylic, caproic, and capric acids. There were 3 replicates per treatment. The quantity of PEDV RNA was determined using qRT-PCR. All main effects, interaction, and comparisons were highly significant (P ≤ 0.001). Liquid Sal CURB and liquid bleach were the most effective chemical treatments to reduce the quantity of detectable PEDV RNA, but their application is limited due to their liquid state and potential corrosiveness. Additional research is necessary to identify the role of sanitizer on PEDV infectivity, even if RNA residue remains, and to develop dry sanitizers capable of removing PEDV RNA on swine feed manufacturing surfaces that are not corrosive.
Keywords: feed manufacturing; chemical sanitation; PEDV